Historia, deporte y sociedad. El futbol en la ciudad de México durante el porfiriato (1892-1910) - Esparza, Miguel (El Colegio de México, A.C., 2023)
The primary objective of this study is to explain the way in which soccer emerged in Mexico City in the period from 1892 to 1910. Rather than being a uniform, linear, planned process, the emergence of soccer in Mexico City must be analyzed as an interdependent, coproduced and unplanned process in which, at different times, a large number of people with different interests from different cities across the country intervened and carried out a series of actions to establish, develop and promote soccer.